Compartment Syndrome A Guide to Diagnosis and Management - Mauffrey, Cyril; Hak, David J.; Martin III, Murphy P. (Springer Nature, 2019)
Compartment syndrome is a complex physiologic process with significant potential harm, and though an important clinical problem, the basic science and research surrounding this entity remains poorly understood. This unique open access book fills the gap in the knowledge of compartment syndrome, re-evaluating the current state of the art on this condition. The current clinical diagnostic criteria are presented, as well as the multiple dilemmas facing the surgeon. Pathophysiology, ischemic thresholds and pressure management techniques and limitations are discussed in detail. The main surgical management strategy, fasciotomy, is then described for both the upper and lower extremities, along with wound care. Compartment syndrome due to patient positioning, in children and polytrauma patients, and unusual presentations are likewise covered. Novel diagnosis and prevention strategies, as well as common misconceptions and legal ramifications stemming from compartment syndrome, round out the presentation. Unique and timely, Compartment Syndrome: A Guide to Diagnosis and Management will be indispensable for orthopedic and trauma surgeons confronted with this common yet challenging medical condition.